A study on the correlation between spatial configuration and rail passenger volume in different scales - take Fuxia region as an example. (2016) - Li, Miaoyi; Shen, Zhenjiang; Sheng, Qiang; Duan, Bingruo; Li, Linglan
Based on the current commercial space distribution data and rail passenger volume of seven cities (Fuzhou, Xiamen, Quanzhou, Zhangzhou, Putian, Fuqing, and Jinjiang) in Fuxia region, this paper analyses the correlation between railway station passenger volume with calculated results of space syntax and commercial space distribution with space syntax segment analysis model. On the macroscopic scale of city group, based on the rail passenger volume of 2011, and the analysed results of population and road traffic space of each city, this study verifies the space syntax segment model's influences on railway station passenger volume in large-scale; on the microscopic scale inside each city, based on the point of interest (POI) data of each function, this study analyses the correlation between functions' spatial aggregation and the mixed transportation system formed by roads and railway stations, and evaluates the degree of functions' distribution influenced by railway station location and relevant spatial parameters. With empirical study, this paper demonstrates space syntax model's possibility and rationality in large regional scale's application, meanwhile, discusses the reason of different results formed by different scales' application, and the future directions for improvement.